Case report: Identification and clinical phenotypic analysis of novel mutation of the PPP1CB gene in NSLH2 syndrome - He, Xuemei; Ma, Xiuli; Wang, Jing; Zou, Zhuo; Huang, Haoyu; Ren, Jian; Liu, Chunming; Zheng, Nan; Ma, Jing; Liu, Yun (Frontiers in Behavioral Neuroscience, 2022)
Objective: To screen and analyze the genetic mutations in the PPP1CB gene in a patient with Noonan syndrome with loose anagen hair-2 (NSLH2) in Yunnan Province, China and explore the possible molecular pathogenesis. Methods: After obtaining informed consent, we collected the patient’s medical history and carried out physical and laboratory examinations for the NSLH2 proband and the family members. Genomic DNA was extracted from the peripheral blood of all individuals. The coding regions including all pathogenic exons, parts of introns, and promoters of genes were sequenced by next-generation sequencing. Pathogenic mutations, which were detected in the probands and their parents, were verified by Sanger sequencing. Results: The clinical manifestations of NSLH2 included prominent forehead, yellowish hair, slightly wide eye distance, sparse eyebrows, bilateral auricle deformity, reduced muscle tension, and cardiac and visual abnormalities. The proband carried a c.371A>G mutation in exon 3 of PPP1CB, which is a missense mutation. This was a de novo mutation as the parents of the proband showed no mutation at this site. Conclusion: In this study, we identified a novel mutation of PPP1CB, which enriched the mutation spectrum of the PPP1CB gene and provided a basis for the diagnosis of NSLH2.